Formation and Evolution of Sandy Island in Front of the Thu Bon River Mouth, Quang Nam Province - Van Phai, Vu; Liem, Ngo Van; Hoang Hai, Pham; Thi Thanh Ha, Vu; Van Binh, Tran; Thi Thanh Nga, Pham; Thu Nhung, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 2, 2023)
The main objective of this paper is to investigate the mechanism of formation and evolution of a river mouth island in front of Cua Dai - a mouth of Vu Gia - Thu Bon river system. The combination of coastal morphodynamic analysis with remote sensing, mapping and GIS methods has shown that the formation and evolution of this island depends on a long-term and complex interaction between the dynamics of the Vu Gia - Thu Bon river system and the coastal littoral, including the Cu Lao Cham archipelago. This process has three stages: i) The formation of river mouth bar; ii) The formation of island in front of the river mouth; and iii) The deformation of island morphology in front of the river mouth. The materials that formed Cua Dai island are not only carried out by the Vu Gia - Thu Bon river system, but also from longshore sediment due to coastal and estuary erosion, mainly from the northern part of Cua Dai. Based on the interaction between material factors (river and longshore sediments) and energy (sea and river dynamics), the evolution of the river mouth bar in front of the Cua Dai island may follow one of two trends: i) The Cua Dai island will gradually move closer to the north shore of Cua Dai, erodes over time, then disappear, assuming no major flood in the Vu Gia - Thu Bon river system and wave and flow regimes are as normal as in the period before 2016; or ii) The Cua Dai island will continue to exist and change if there is an increase in climate change, especially extreme events such as storms, floods, and sea level rise.